Legislative framework for the proper carrying out experimental protocols in laboratory animals and the management of carcasses - MONOGIOU (Ε. ΜΟΝΟΓΙΟΥ) E. (Journal of the Hellenic Veterinary Medical Society, 2017)
There is a specific legal, both national and EU framework, that regulates animal testing and cadaver disposal. Indicatively, as far as the National legislation is concerned, the Presidential Decree 160/1991 and the Law 2015/1992 on the validation of the European Convention on the protection of laboratory animals is mentioned. As for the European legislation, the Council Directive 86/609/EEC as well as the Recommendation of the European Commission E (2007) 2525 is mentioned. Animal testing on laboratory animals consists of four actions as defined by meaning: the field of study, the licensing of experimentation (Reduction-Refinement-Replacement), the recommendation of a Commission of Ethics assessment and finally the Cost-benefit analysis. The aims of the above mentioned legislation are the following: reduction in the number of the laboratory animals in use, providing care to them, reduction of the fear and pain, suppress any attempt to avoid the unnecessary repetitions of experimental protocols and, finally, acquirement of alternative methods of research. The cadavers of laboratory animals (considered to be animal by-products) are part of category 1 and are handled accordingly based on the Veterinary legislation (European Regulation 1774/2002, Presidential Decree 211/2006) through the following stages: collection in special collectors, frozen storage, transfer with licensed vehicles and eventually, arrival at a licensed processing unit and final disposal of the material as waste via cremation or burial under hygienic conditions. The proper handling of laboratory animals is documented with many kinds of ancillary material. However, they can be handled also through the Medical Waste Legislation (as dangerous-infectious-toxic waste / category 2) with stages that take place either within or out of health units (Ministerial Decision 8668/2007, Joint Ministerial Decision 24944/1159) as follows: firstly, collection in appropriate confection and frozen storage, followed by transfer by licensed vehicles to a licensed unit, followed by cremation or sterilization and finally, disposal through burial under hygienic conditions. This way of handling of laboratory animals is documented by many kinds of subsidiary material. The Veterinary legislation, as well as the legislation concerning public health, imposes serious penalties to any violators. The current legal framework is accepted as the foundation which provides a basis for any efforts (a) improving care on the assessment of the cost/living quality ratio of laboratory animals, (b) substitution of these animals with alternative methods of research and (c) protection of the environment, in general, through the proper handling / traceability of the cadavers of the animals that are part of experiments.